1986
DOI: 10.1111/j.1365-3059.1986.tb01979.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of powdery mildew (Erysiphe graminis f. sp. hordei) and leaf rust (Puccinia hordei) on spring barley in New Zealand. I. Epidemic development, green leaf area and yield

Abstract: Powdery mildew and leaf rust caused large yield losses in spring barley grown near Christchurch, New‐Zealand, in two seasons. Disease present during early growth stages was as damaging to yield as disease late in the season. Moderate leaf rust severities after anthesis were most damaging when combined with earlier mildew epidemics. Later growth did not compensate for reduced yield potential induced by early infection. This was attributed, at least in part, to an effect on leaf size, and therefore on green leaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
2

Year Published

1989
1989
2014
2014

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 17 publications
(21 reference statements)
3
30
0
2
Order By: Relevance
“…The effect of disease on the number of ears was associated with reduced tiller production rather than tiller survival, suggesting an effect early in the crop growth cycle (Whelan, 1992). This has not been shown previously in New Zealand barley crops infected by leaf rust (Lim & Gaunt, 1986a). Powdery mildew did reduce ear populations, but this was via tiller survival rather than via tiller production (Lim & Gaunt, 1986a).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The effect of disease on the number of ears was associated with reduced tiller production rather than tiller survival, suggesting an effect early in the crop growth cycle (Whelan, 1992). This has not been shown previously in New Zealand barley crops infected by leaf rust (Lim & Gaunt, 1986a). Powdery mildew did reduce ear populations, but this was via tiller survival rather than via tiller production (Lim & Gaunt, 1986a).…”
Section: Discussionmentioning
confidence: 64%
“…This has not been shown previously in New Zealand barley crops infected by leaf rust (Lim & Gaunt, 1986a). Powdery mildew did reduce ear populations, but this was via tiller survival rather than via tiller production (Lim & Gaunt, 1986a). In most field crops leaf rust develops too late for effects on tiller development, but early infections in late sown crops may affect tiller development in some years .…”
Section: Discussionmentioning
confidence: 70%
“…The importance of this mechanism depends strongly on the development stage of the crop, since the underlying positive feedback between crop growth, leaf area formation and radiation interception is strongest during early growth stages (Blackman, 1919). Previously, Lim and Gaunt ( 1986) and Van Oijen ( 1991) pointed at the importance of the available leaf area at initiation of a disease for leaf area duration and cumulative radiation interception. It can be concluded that the difference in LAI at the initiation of leaf blast, caused by the difference in inoculation elate, was the most prominent factor responsible for the observed differences in total dry matter production of the inoculated treatments in this experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Powdery mildew and rust are very widespread diseases, causing potential problems basically everywhere where barley is grown. Without control by plant resistance genes or fungicides, they often cause moderate to severe yield reduction although they are not devastating (Lim and Gaunt 1986). Two important aspects of their success are (1) the enormous epidemiological potential due to massive production of asexual spores that can be transported by wind over distances of hundreds of kilometres and (2) an intact sexual life cycle rendering them capable of combining beneficial alleles and rapidly adapting to challenges opposed, e.g.…”
Section: Response To Biotrophic Pathogensmentioning
confidence: 99%